SMALL BRITISH SCHOOLS: THE WILL TO SURVIVE - Edmonds, E.L. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1991)
Once again, the small school in Britain faces an uncertain future. Under the Education Reform Act or 1988 a National Curriculum has been prescribed for all schools. It consists of ten foundation subjects. Three are called core subjects: English, math, and science. The others are technology (including design), history, geography, music, art, physical education, and for those aged 11 to 16, a modern foreign language. These are not the complete curriculum, which will include at certain stages such things as health education, personal and social education, and career guidance. Attainment targets have been set, traversing the whole spectrum of knowledge, skills, and understanding which pupils should master as they progress through the school. There are four key-stages at ages 7, 9, 11, and 14, when School Attainment Tests will he set. The question therefore is being asked, "How can small schools with two or three teachers possibly offer such a broad, differentiated curriculum?" Is not closure in favour of consolidation into larger units the only answer? Apparently, the small primary schools themselves do not think so, nor do their supporters. A few have closed their doors under local education authority re-organization. But, thus far, the great majority have stayed open for business and are very much alive, if still apprehensive. How do they do it? Where does their support come from?